Juvenile Criminal Responsibility in Muslim-Majority States: Between Sharia, State Law, and Restorative Justice - Julisa Aprilia Kaluku; Nurini Aprilianda; Prija Djatmika; Alfons Zakaria; Fatiha Gourari (De Jure: Jurnal Hukum dan Syari'ah, 2026)
Juvenile justice in Muslim-majority jurisdictions reveals a persistent normative tension between Sharia-based conceptions of criminal responsibility, state-centred legal regulation, and international child protection standards. This article comparatively examines juvenile criminal sanction policies in Saudi Arabia, Egypt, Pakistan, and Indonesia, with primary attention to the construction of criminal responsibility, models of sanctioning, institutional responses, and the place of community-based restorative mechanisms. Using a comparative approach, the study analyses how these jurisdictions negotiate the relationship between Islamic legal principles, national legislation, and culturally embedded local wisdom in responding to children in conflict with the law. The findings identify three general patterns: a predominantly punitive Sharia-oriented framework, a statutory-rehabilitative framework, and a hybrid framework combining legal reform with suboptimal local implementation. Among the four jurisdictions, Indonesia occupies a distinctive position because it institutionalises diversion and restorative justice while also allowing for socially grounded forms of reconciliation. With reference to this comparative synthesis, the article advances Dumot Justice as its principal conceptual contribution—a restorative-pluralist framework that integrates child protection, victim restoration, social accountability, and communal balance within a rights-sensitive juvenile justice design. The study concludes that sustainable juvenile justice reform in Muslim jurisdictions requires a jurisprudential model that integrates Sharia, national law, child protection, and culturally embedded restorative practices. Keywords: restorative justice; Islamic law; comparative legal analysis; child right protection.